Why are the Other Non-Tax State Revenue Budget Variances in Ministries and Agencies in Indonesia Large? Any Dysfunctional Behaviour? - Halim, Abdul; Sari, Poppy Danastri; Sofyani, Hafiez (The Indonesian Journal of Accounting Research, 2024)
This study investigated the cause of significant variance in the revenue budget realization of Other Non-Tax State Revenues (NTSRs) in ministries and agencies in Indonesia. This study employed a qualitative research approach by conducting in-depth interviews with 13 informants from relevant authorities, followed by some document analyses. The results discovered that the causes of the variance in revenue budget from Other NTSR of State Ministries and Agencies could be divided into three: 1) uncontrolled factors, covering difficulty predicting certain NTSR types, external factors, unexpected service requests, and political factors; 2) controlled factors, including mapping of potential revenue, the tendency of dysfunctional behavior (budgetary slack, cherry-picking, myopia, ratchet), expenditure resource dilemma, lack of human resources capacity and capability, and poor supervision of NTSR planning; and 3) regulation/policy changes from upper-level authority. This study fills a gap in identifying factors that trigger government budget variance problems on other NTSRs that often occur in developing countries such as Indonesia. This study also adds insight into how agency problem patterns occur at the ministry and agency level in budgeting practices